Gender equality and workplace diversity in a school division office - Asher G. Cristales; Ismael A. Haguisan III; Geff B. Sagala (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2023)
Gender equality promotes equal rights, responsibilities, and opportunities for all genders. Nowadays, organizations are adopting a globally competitive environment with programs that promote diversity, inclusion, and non-discrimination policies. This study aimed to determine the extent of the practice of gender equality and workplace diversity in a School Division Office. The respondents were 110 non-teaching employees who completed a research questionnaire. This study utilized a descriptive comparative-correlational research design. The results indicated a high extent of practice for gender equality and an even higher extent for workplace diversity. Additionally, the results revealed a significant relationship between gender equality and workplace diversity. Therefore, employees demonstrate a commitment to practicing gender equality within their diverse workplace, fostering a multicultural setting.